Quality of information and communications technology : 13th International Conference, QUATIC 2020, Faro, Portugal, September 9-11, 2020, proceedings /: 13th International Conference, QUATIC 2020, Faro, Portugal, September 9-11, 2020, proceedings. (2020) - Unknown
No abstract available